The PPPY Motif of Human T-Cell Leukemia Virus Type 1 Gag Protein Is Required Early in the Budding Process - Le Blanc, Isabelle (American Society for Microbiology, 2002)
Domains required late in the virus budding process (L domains) have been identified in the Gag proteins of a number of retroviruses. Here we show that the human T-cell leukemia virus type 1 candidate L domain motif PPPY is indeed required for virus production. Strikingly, however, mutation of this motif arrested virus particles at an earlier stage in the budding process than was seen for mutation of the L domain motifs thus far described for retroviruses. In view of the exchangeability of such domains, we propose that the retrovirus budding process may involve a continuum from bud formation to membrane fission.